Decrease in Sightings of Sixgill Sharks, Hexanchus griseus, in Elliott Bay, Seattle, WA, United States, a Comparison Between 2003–2005 and 2008–2015 - Griffing, Denise; Christiansen, Jeff; Hollander, Joel; Carpenter, Tim; Larson, Shawn (Frontiers in Marine Science, 2019)
The Bluntnose Sixgill Shark, Hexanchus griseus, is a large predatory shark, has a worldwide distribution and is listed as near-threatened by the International Union of Conservation of Nature (IUCN). The Seattle Aquarium collected observations of free-swimming Sixgill Sharks in Elliott Bay, Washington, under the aquarium’s pier in 20 m of water from 2003 to 2005 and again from 2008 to 2015 using the same methodology. Compared to total Sixgill sightings between 2003-2005 (273) fewer total Sixgills were sighted at the aquarium’s research station between 2008-2015 (33). The reason for the observed decline in sightings in unknown but based on data from other studies on Sixgills in Puget Sound during the same timeperiod the authors hypothesize the decrease may be due to natural variability of juvenile Sixgill recruitment to Elliott Bay.